2003
DOI: 10.1103/physrevc.67.022801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tunneling on electron screening in low energy nuclear reactions in laboratories

Abstract: Using a semiclassical mean field theory, we show that the screening potential exhibits a characteristic radial variation in the tunneling region in sharp contrast to the assumption of the constant shift in all previous works. Also, we show that the explicit treatment of the tunneling region gives a larger screening energy than that in the conventional approach, which studies the time evolution only in the classical region and estimates the screening energy from the screening potential at the external classical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…We notice in passing that event A is a case where cylindrically symmetry is approximately satisfied, because the electron motion is practically on the xy−plane. This case gives a U e =19.5eV closest to the adiabatic limit and to the TDHF result [6,7].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…We notice in passing that event A is a case where cylindrically symmetry is approximately satisfied, because the electron motion is practically on the xy−plane. This case gives a U e =19.5eV closest to the adiabatic limit and to the TDHF result [6,7].…”
supporting
confidence: 69%
“…The comparison between newly obtained bare cross sections, i.e., astrophysical S-factors, and the cross sections by the direct measurements gives a variety of values for the screening potential. There are already some theoretical studies performed using the time-dependent Hartree-Fock(TDHF) scheme [6,7].In this letter we examine the subject within the constrained molecular dynamics (CoMD) model [8], even in the very low incident energy region not reached experimentally yet. At such very low energies fluctuations are anticipated to play a substantial role.…”
mentioning
confidence: 99%
“…where U (g) e = 40.7 eV and U (u) e = 0.0 eV [11,10]. If we take into account the electron capture of the projectile, i.e., in the case of D+D, the enhancement factor in the adiabatic limit is…”
Section: Constrained Molecular Dynamicsmentioning
confidence: 99%
“…These values are often smaller than the sudden limit or larger than the adiabatic limit. Theoretical studies performed using the time-dependent Hartree-Fock (TDHF) scheme [10,11] suggest that the screening potential is between the sudden and the adiabatic limits.…”
Section: Introductionmentioning
confidence: 99%
“…44) Any enhancement of the probability due to the break-up of the nuclei is also too small. 45) In this conference Kimura showed that the screening potential may exhibit a radial variation in the tunneling region, 46) which may increase the screening energy to beyond the adiabatic limit. Unfortunately this is not a satisfactory solution since this result depend on the excited state components.…”
Section: One Obtainsmentioning
confidence: 99%